Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13112696
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming PD-1 Inhibitor Resistance with a Monoclonal Antibody to Secreted Frizzled-Related Protein 2 in Metastatic Osteosarcoma

Abstract: Secreted frizzled-related protein 2 (SFRP2) promotes the migration/invasion of metastatic osteosarcoma (OS) cells and tube formation by endothelial cells. However, its function on T-cells is unknown. We hypothesized that blocking SFRP2 with a humanized monoclonal antibody (hSFRP2 mAb) can restore immunity by reducing CD38 and PD-1 levels, ultimately overcoming resistance to PD-1 inhibitors. Treating two metastatic murine OS cell lines in vivo, RF420 and RF577, with hSFRP2 mAb alone led to a significant reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Nasarre et al. ( 87 ) investigated the role of a monoclonal antibody targeting humanized secreted frizzled-related protein 2, a protein that promotes angiogenesis and metastasis, in metastatic osteosarcoma resistance to PD-1/PD-L1 inhibitors, and its impact on T cells. They found that humanized secreted frizzled-related protein 2 monoclonal antibody inhibited T cell proliferation and osteosarcoma metastasis by lowering the expression of NFATc3, CD38, and PD-1.…”
Section: Cellsmentioning
confidence: 99%
“…Nasarre et al. ( 87 ) investigated the role of a monoclonal antibody targeting humanized secreted frizzled-related protein 2, a protein that promotes angiogenesis and metastasis, in metastatic osteosarcoma resistance to PD-1/PD-L1 inhibitors, and its impact on T cells. They found that humanized secreted frizzled-related protein 2 monoclonal antibody inhibited T cell proliferation and osteosarcoma metastasis by lowering the expression of NFATc3, CD38, and PD-1.…”
Section: Cellsmentioning
confidence: 99%
“…Secreted frizzled-related protein 2 (SFRP2) promotes the migration of tumor cells and tube formation in endothelial cells, which are associated with OS metastasis. An in vitro study showed that a monoclonal antibody against SFRP2 combined with a PD-1 antibody synergistically inhibited the metastasis of OS ( Nasarre et al, 2021 ). Recruitment of MDSCs to the TME inhibits the effect of anti-PD1 therapy.…”
Section: New Therapeutic Methodsmentioning
confidence: 99%
“…Very few studies have been published in which the authors detected established metastases in the lungs of mice by microscopy (in pilot experiments) and/or in vivo imaging before beginning treatment. Nasarre et al observed additive cooperation between PD-1 inhibitor and an antibody targeting Secreted Frizzled-Related Protein 2 (SFRP2) to reduce the number of metastases on the surface of mouse lungs by commencing treatment mice with the antibody in conjunction with a PD-1 inhibitor eight to twelve days after cells were intravenously injected [ 164 ]. The proteasome inhibitor ixazomib inhibited the growth of established pulmonary metastases after their presence was confirmed by bioluminescence imaging in two xenograft models, and moderately enhanced survival [ 165 ].…”
Section: Animal Studiesmentioning
confidence: 99%